2010
DOI: 10.1039/c0cc00638f
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia N–H activation by a N,N′-diamidocarbene

Abstract: The synthesis and characterization of N,N'-dimesityl-4,6-diketo-5,5-dimethylpyrimidin-2-ylidene is reported; this crystalline N,N'-diamidocarbene was found to split ammonia and engage in other reactions not exhibited by typical N-heterocyclic carbenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
109
0
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(116 citation statements)
references
References 33 publications
(13 reference statements)
4
109
0
3
Order By: Relevance
“…Note that although di(amido)carbenes c DAC , react with CO and NH 3 (vide infra), they are inert towards hydrogen even under forcing conditions (65 atm H 2 , 200 °C). 25 …”
Section: Activation Of Small Moleculesmentioning
confidence: 99%
“…Note that although di(amido)carbenes c DAC , react with CO and NH 3 (vide infra), they are inert towards hydrogen even under forcing conditions (65 atm H 2 , 200 °C). 25 …”
Section: Activation Of Small Moleculesmentioning
confidence: 99%
“…Continuing our investigations, we observed that the very weakly acidic diethylamine and diethylphosphine are cleaved at room temperature, affording adducts 12 and 13, in 78 and 56 % yield, respectively [17] (Scheme 4). In contrast, phenylacetylene, which is more acidic, does not react with 1.…”
mentioning
confidence: 97%
“…(4) The ability of the hydrogen adduct 4H to store hydrogen is also enhanced with the substitution of electrondonating groups on N 2 and N 5 . [36][37][38][39]. For example, Lee et al [36] discovered that N,N′-diamidocarbenes are ambiphilic and can behave as electrophiles and nucleophiles.…”
Section: Discussionmentioning
confidence: 97%